Information Transparency and Investor Protection in Building Investor Confidence and Informing Investment Decisions in Equity Crowdfunding in Indonesia - Abdul Karim; Salwa Aulia Novitasari; Dila Padila Nurhasanah (West Science Interdisciplinary Studies, 2026)
The rapid growth of equity crowdfunding in Indonesia has introduced new opportunities for public participation in investment activities while simultaneously creating challenges related to information uncertainty, investor vulnerability, and trust formation. Unlike conventional investment markets, equity crowdfunding involves greater information asymmetry because investors often evaluate privately held businesses with limited operational history and incomplete information. Therefore, mechanisms that enhance information transparency and investor protection are essential to strengthening investor confidence and supporting rational investment decisions. This study aims to examine the influence of information transparency and investor protection on investment decision-making through the mediating role of investor trust in the context of equity crowdfunding in Indonesia. This research employs a quantitative approach using survey data collected from 100 equity crowdfunding investors in Indonesia. Data were gathered through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that information transparency has a positive and significant effect on investor trust, while investor protection demonstrates a stronger positive influence on investor trust. Furthermore, investor trust significantly affects investment decision-making. Information transparency and investor protection also directly influence investment decision-making, with investor trust partially mediating these relationships. The findings demonstrate that transparent information disclosure and effective protection mechanisms are critical factors in reducing uncertainty, strengthening investor confidence, and encouraging participation in equity crowdfunding markets. This study contributes to the fintech and investment behavior literature by highlighting the importance of governance mechanisms in developing a trustworthy and sustainable equity crowdfunding ecosystem in emerging markets such as Indonesia.